Keterbukaan Diri (Self Disclosure) pada Remaja Dewasa Perempuan terhadap Lawan Jenis - Safira Amadea Yunita; Ruth Mei Ulina Malau (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2023)
Self-Disclosure is the attitude of individuals who are able and willing to provide information about themselves privately and openly and are willing to accept the opinions of others by trusting someone to share with. This study aims to describe the meaning of self-disclosure of young adult girls to the opposite sex on the Bumble Online dating application. This study uses a constructivist paradigm with a descriptive qualitative approach and the research location is in the City of Bandung. The data collection method used was in the form of interviews and documentation of research subjects to several six key informants. The results of this study indicate that users of the Bumble application allow for self-disclosure of each user based on the form of interaction carried out by the user so that it creates encouragement for everyone to express himself. Factors that can influence adolescent self-disclosure can be seen from the intensity of user chats in the application and how other people respond to each exchange of messages that occur. The conclusion of this study is that self-disclosure in young adult girls is pseudo-openness (Online openness). Because through the Bumble application they only show the positive side of themselves. Keywords: Application, Online Dating, Self Disclosure